Pengaruh Benson Terhadap Nyeri Insersi pada Pasien yang Menjalani Hemodialisa di RSUD Kota Tanjungpinang - Irawati Irawati; Sri Muharni; Utari Christya Wardhani (Akademi Analis Kesehatan Pekalongan, 2023)
Insertion pain is pain caused by the action of inserting a needle into the AV fistula as a link between blood vessel circulation and the hemodialysis machine during the hemodialysis process. In Brazil it was found that 70% of patients undergoing hemodialysis experienced mild to moderate pain at the time of AV fistula insertion. The phenomenon found in the hemodialysis unit at Tanjungpinang City Regional Hospital in 2020 was 33 patients experiencing moderate pain. This research was conducted to determine the effect of the Benson relaxation technique on pain during insertion in patients undergoing hemodialysis. The research method is a quasi experimental design, with a pre test – post test design approach without control group. The sample consisted of 30 respondents in the intervention and control groups who were routine hemodialysis patients at the Tanjungpinang City Regional Hospital in 2023. Using a non-probability sampling technique, consecutive sampling. Data were processed using the Wilcoxon signed rank test. Univariate analysis of results before the Benson technique, 73.3% experienced moderate pain and after the Benson technique, 80% did not feel pain in the intervention group. It was concluded that there was an influence of the Benson technique on insertion pain in patients undergoing hemodialysis. It is hoped that the Benson relaxation technique will be applied by nurses as non-pharmacological pain management to reduce AV-fistula insertion pain in hemodialysis patients.